SMARTPHONE USE IN LEARNING AS PERCEIVED BY UNIVERSITY UNDERGRADUATES: BENEFITS AND BARRIERS - Masadeh, Thouqan Saleem Yakoub (International Journal of Research -GRANTHAALAYAH, 2021)
Smartphones are attractive tools for the majority of young people particularly university undergraduates and integrating them in learning is something valuable. Nevertheless, they might do harm to their achievement if the use barriers and bad effects are not identified. Motivated by this idea, the present study was undertaken. Participants were (42) university undergraduates at the departments of mathematics and English language at Najran University in the first semester of the academic year 2020/2021. Findings showed that students were agreeable to smartphone usefulness, ease of use, and barriers. However, their responses to the effects of smartphone use were not clear. The majority of them were neutral, i.e., could not decide whether smartphones affect their learning or not. In light of these results, the study concluded that smartphone technology integration in learning is very crucial but when barriers and bad effects are clear to both teachers and students.